Spatial and seasonal distributions of ten species of benthic macrofauna and twelve water environmental factors in a subtidal zone near the Daya Bay nuclear power plant - Cai, Lizhe; Rao, Yiyong; Zhao, Xiaoyu; Yang, Deyuan; Zhou, Xiping; Wang, Deli; Yue, Xinli (Frontiers in Marine Science, 2023)
In this study, we analyzed the spatial and seasonal distributions of ten species of benthic macrofauna and 12 water environmental parameters at thirty-six sampling stations in the subtidal zone near the Daya Bay Nuclear Power Plant. The results showed that there were four types of distribution characteristics for 10 species of macrobenthic animals and 12 water environmental factors near the Daya Bay nuclear power plant: (1) three species of benthic macrofauna, namely Apionsoma (Apionsoma) trichocephalus, Amphioplus (Lymanella) laevis, and P. bidentata, and six water environmental parameters, including water depth, salinity, dissolved oxygen, suspended solids, chromium, and lead increased from inside the bay to outside the bay. (2) Three species of benthic macrofauna, P. cristata, T. lata, and T. scabra, and four water environmental parameters, including oils, arsenic, total phosphorus, and silicate, decreased from inside to outside the bay. (3) Two species of benthic macrofauna, A. dibranchis, and P. undulatus and one water environmental parameter, pH, were higher in the central bay than inside and outside the bay. (4) One species of benthic macrofauna, Sigambra hanaokai, and one water environmental parameter, total nitrogen, were lower in the central bay than inside and outside the bay. Correlation and BIO-ENV analyses confirmed that water depth was the main environmental factor affecting the ten species of benthic macrofauna. Understanding the distributions of the dominant benthic macrofauna could help protect nuclear cold source systems from benthic macrofaunal blockage and explore marine ecosystem connectivity.